2019
DOI: 10.3390/ijms20051097
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Pre-Conditioning Enhances the Stem Cell Phenotype of Human Bone Marrow Stem/Progenitor Cells

Abstract: A deeper understanding of the detailed mechanism of in vivo tissue healing is necessary for the development of novel regenerative therapies. Among several external factors, environmental pH is one of the crucial parameters that greatly affects enzyme activity and cellular biochemical reactions involving tissue repair and homeostasis. In this study, in order to analyze the microenvironmental conditions during bone healing, we first measured the pH in vivo at the bone healing site using a high-resolution fiber o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…It has been reported that calcium ions stabilize or enhance the viability of dental pulp cells [ 44 ], periodontal ligament cells [ 45 ], and odontoblasts [ 46 ]. Additionally, pH is also an important factor that influences the wound healing process by changing throughout the process [ 47 , 48 , 49 ]. In our previous study, we revealed that periodontal ligament cells, and osteoblast-like cells cultured with the prototype of CS-BG within the pH range of 9 to 10 had no adverse effects [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that calcium ions stabilize or enhance the viability of dental pulp cells [ 44 ], periodontal ligament cells [ 45 ], and odontoblasts [ 46 ]. Additionally, pH is also an important factor that influences the wound healing process by changing throughout the process [ 47 , 48 , 49 ]. In our previous study, we revealed that periodontal ligament cells, and osteoblast-like cells cultured with the prototype of CS-BG within the pH range of 9 to 10 had no adverse effects [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…osteosarcoma [52], and the maintenance of stemness in mesenchymal cells [53,54]. Also, OCT-4 expression in murine fibroblasts increases as pH shifts from 7.4 to 6.5 [55].…”
Section: Discussionmentioning
confidence: 99%
“…This SMH/GO-promoted BMSCs migration and osteogenic differentiation was tightly associated with the degradation products of hydrogels. Normally, BMSCs are recruited to wound sites by chemokines and pro-inflammatory cytokines at the early stage of bone healing 49. The recruited BMSCs mineralize (mineralized nodules formation is a typical marker for BMSCs osteogenic differentiation) and differentiate into osteoblasts in the presence of an array of cytokines, thus promoting bone repair.…”
Section: Discussionmentioning
confidence: 99%